Peranan Keluarga Sakinah dalam Pembinaan Akhlak Karimah pada Anak (Studi Pemikiran Abdullah Nashih dan Abdurrahman An Nahlawi) - Khairun Nita Aulia (CV. Creative Tugu Pena, 2024)
The family has a strategic role in developing good morals in children. Parents must create a sakinah mawaddah warahmah family as the basis for moral education. Currently, it is difficult to find a family that makes the home the center of their children's moral education. The formulation of the research problem is